Evaluation of the effectiveness of ultrasound-guided transversus abdominis plane (TAP) block for chronic pain after lower abdominal surgery - Güngör Enver Özgencil; Dostali Aliyev; Ümit Akkemik (Genel Tıp Dergisi)
Aim: This study aimed to evaluate the effectiveness of ultrasound-guided transversus abdominis plane (TAP) block in patients diagnosed with chronic pain after undergoing lower abdominal surgery. Methods: Patients who were admitted to the pain medicine clinic between January 1, 2016, and January 1, 2020, and underwent TAP block with the diagnosis of chronic pain after undergoing lower abdominal surgery were retrospectively analyzed. The visual analog scale (VAS) score was measured before the procedure and at the 1-month and 3-month follow-ups. Results: The proportion of patients with a reduction in VAS scores of >50% after TAP block application was 50% at the 1-month follow-up and 72.5% at the 3-month follow-up. The changes in the VAS score was found to be statistically significant (p < 0.05). Conclusion: Although ultrasound-guided TAP block seems to be an effective treatment method for chronic pain after lower abdominal surgery, further studies and clinical trials investigating different types of surgeries and including a larger number of patients are warranted.